A Brain‐wide association study of DISC1 genetic variants reveals a relationship with the structure and functional connectivity of the precuneus in schizophrenia. Issue 11 (7th June 2014) - Gong, Xiaohong; Lu, Wenlian; Kendrick, Keith M.; Pu, Weidan; Wang, Chu; Jin, Li; Lu, Guangmin; Liu, Zhening; Liu, Haihong; Feng, Jianfeng
Abstract The Disrupted in Schizophrenia Gene 1 (DISC1) plays a role in both neural signaling and development and is associated with schizophrenia, although its links to altered brain structure and function in this disorder are not fully established. Here we have used structural and functional MRI to investigate links with six DISC1 single nucleotide polymorphisms (SNPs). We employed a brain‐wide association analysis (BWAS) together with a Jacknife internal validation approach in 46 schizophrenia patients and 24 matched healthy control subjects. Results from structural MRI showed significant associations between all six DISC1 variants and gray matter volume in the precuneus, post‐central gyrus and middle cingulate gyrus. Associations with specific SNPs were found for rs2738880 in the left precuneus and right post‐central gyrus, and rs1535530 in the right precuneus and middle cingulate gyrus. Using regions showing structural associations as seeds a resting‐state functional connectivity analysis revealed significant associations between all 6 SNPS and connectivity between the right precuneus and inferior frontal gyrus. The connection between the right precuneus and inferior frontal gyrus was also specifically associated with rs821617. Importantly schizophrenia patients showed positive correlations between the six DISC‐1 SNPs associated gray matter volume in the left precuneus and right post‐central gyrus and negative symptom severity. No correlations with illness duration were found. Our results provide the first evidence suggesting a key role for structural and functional connectivity associations between DISC1 polymorphisms and the precuneus in schizophrenia. Hum Brain Mapp 35:5414–5430, 2014. © 2014 Wiley Periodicals, Inc.